Studi Awal Pembuatan Polymer Matrix Composite (PMC) Epoksi yang Didoping Nanopartikel ZnO sebagai Material Antibakteri - Manty Aldilani Ikaningsih; Ghazi Alwan Rafi; Djoko Hadi Prajitno (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2022)
Bacteria that stick to and accumulate on the toothbrush can cause infection or disease in the oral cavity. Therefore, many antibacterial materials are being researched to inhibit bacterial growth, even kill bacteria. In this preliminary research, polymer matrix composite with an epoxy matrix doped with ZnO nanoparticles was carried out as an antibacterial material on toothbrushes. The epoxy matrix, hardener, and ZnO nanoparticles are mixed until they are homogeneous and then printed like a toothbrush. The ratio of resin and hardener varied 1R:1H and 2R:1H with variations of ZnO are 0%; 0.6% and 0.9%. XRD, hardness, FTIR, and bending tests have been carried out to determine the characteristics of PMC. The hardness of PMC with ZnO 0%; 0.6%; 0.9% respectively are 55.6; 58.5; 60.5 for 1R:1H and 73.3; 74.3; 74.8 for 2R:1H. Testing for antibacterial properties using a spectrophotometer with the optical density method was carried out to determine the antibacterial. The highest antibacterial properties were PMC with ZnO 0.9% 2R:1H. Based on data, it was found that the hardness was getting higher along with the increasing ZnO nanoparticles and the ratio of resin. For testing antibacterial properties, increasing ZnO nanoparticles resulted in an increase in the antibacterial properties.